ANALISIS KETERSEDIAAN DEBIT UNTUK KEBUTUHAN IRIGASI PRIMER JURANG BATU KECAMATAN PRAYA TENGAH KAB. LOMBOK TENGAH - ANDRIA FIRMANSYAH BATARA; MUHAMAD YAMIN; AMINULLAH AMINULLAH (SOSIAL SAINS DAN TEKNOLOGI, 2023)
The purpose of this study was to determine the bending discharge of the Jurang Batu, to calculate the availability and demand for primary irrigation water in the Jurang Batu, and to calculate the discharge in the primary channel of the Jurang Batu irrigation. This type of research is case study research. This research was started with the first step, namely a field survey, in addition to conducting field surveys, primary data collection was also carried out by interviewing branch heads and secondary data collection from the Pompengan Balai Besar, followed by analyzing weir discharge data, evapotranspiration data and effective rainfall. The results of this study indicate that the availability of water in the primary irrigation of Jurang Batu for the 1st planting season starting from the preparation of land preparation until the growth period for rice plants is still sufficient where the required water discharge is 272.74 l/sec/ha while the availability is 1699.75 l/sec/ Ha. The discharge in the Jurang Batu primary channel is 569,613 l/s.